SOCIO-ECONOMIC ANALYSIS OF CASSAVA PRODUCTION IN IKOLE LOCAL GOVERNMENT AREA OF EKITI STATE. - TOLUWASE, S.O.W; ABDU-RAHEEM, K. A (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The study was carried out in Ikole Local Government Area of Ekiti State. Structured questionnaire was used to collect data on socio-economic variables, costs and revenues of the farmers. One hundred food crop famers cultivating cassava were randomly selected for the study. The result revealed that most of the farmers were young and educated. The mean household size was eight people. Land tenure through inheritance was the major method of acquiring farmland. Most farmers are small scale farmers operate mostly on owners equity. The gross margin of cassava production was #172, 920.00 per hectare. Cassava production was profitable by returning 2.07 for everyone naira invented in the study area. Among the recommendation made to boost production in the area was granting of small loans to farmers by commercial banks and land should be made available and allocated to the farmers to increase output and productivity of cassava production in the study area.